THE SPEECH ACCOMMODATION STRATEGIES OPTED BY MIGRANT STUDENTS IN SURABAYA - Anjanillah, Farah (Yayasan Nuraini Ibrahim Mandiri, 2024)
The social conditions of Indonesia as multilingual and multicultural might lead to the emergence of language variations such as dialects. Nevertheless, those dialects could affect the mutual intelligibility between the speaker and the interlocutor (Wardhaugh & Fuller, 2015). From this case, the researcher is attracted to undertake a study exploring the strategies applied by migrant students from many regions in East Java to accommodate Surabayan dialect along their undergraduate degree journey in Surabaya. This study aims to sketch out the forms, strategies and motives underlying speech accommodation by employing the theoretical framework of Giles & Powesland (1975), Giles et al’s (1979) and Coupland et al (1988). The data were obtained through a questionnaire. The results of the study showcase that the migrant students employed convergence and divergence strategy to accommodate Surabayan dialect indicated in numerous word classes. The forms of speech accommodation include upward and long-term adjustment (Dragojevic et al, 2016). Meanwhile, in terms of motive, it involves affective and cognitive motive (Dragojevic et al, 2016). Besides, the respondents also applied interpretability and approximation strategy (Coupland et al, 1988). To wrap those all up, it could be grasped that the application of speech accommodation strategies are affected by external factors of language such as social distance, prestige, with whom and where the interaction occurs (Wijana & Rohmadi, 2013; Gnisci et al, 2016; Palomares et al, 2016).